Arabidopsis AtbHLH112 regulates the expression of genes involved in abiotic stress tolerance by binding to their E‐box and GCG‐box motifs. Issue 3 (1st April 2015) - Liu, Yujia; Ji, Xiaoyu; Nie, Xianguang; Qu, Min; Zheng, Lei; Tan, Zilong; Zhao, Huimin; Huo, Lin; Liu, Shengnan; Zhang, Bing; Wang, Yucheng
Summary Plant basic helix–loop–helix (bHLH) transcription factors play essential roles in abiotic stress tolerance. However, most bHLHs have not been functionally characterized. Here, we characterized the functional role of a bHLH transcription factor from Arabidopsis, AtbHLH112, in response to abiotic stress. AtbHLH112 is a nuclear‐localized protein, and its nuclear localization is induced by salt, drought and abscisic acid (ABA). In addition, AtbHLH112 serves as a transcriptional activator, with the activation domain located at its N‐terminus. In addition to binding to the E‐box motifs of stress‐responsive genes, AtbHLH112 binds to a novel motif with the sequence 'GG[GT]CC[GT][GA][TA]C' (GCG‐box). Gain‐ and loss‐of‐function analyses showed that the transcript level of AtbHLH112 is positively correlated with salt and drought tolerance. AtbHLH112 mediates stress tolerance by increasing the expression of P5CS genes and reducing the expression of P5CDH and ProDH genes to increase proline levels. AtbHLH112 also increases the expression of POD and SOD genes to improve reactive oxygen species (ROS) scavenging ability. We present a model suggesting that AtbHLH112 is a transcriptional activator that regulates the expression of genes via binding to their GCG‐ or E‐boxes to mediate physiological responses, including proline biosynthesis and ROS scavenging pathways, to enhance stress tolerance.